Sanções administrativas em contratos de serviços: análise multicritério como auxílio à gestão em uma instituição federal de ensino - Nepomoceno, Francielle Correa (2024)
Introduction: Both public and private companies use outsourcing to optimize and improve services. Contracts in the Brazilian public service are made through bidding processes that are regulated by specific laws, which also supervise these contracts. In order to ensure oversight, public agents are responsible for a series of tasks. One of these tasks is the application of administrative penalties and sanctions in the event of irregularities in the execution of contracts. Problem: As a result, one of the pillars of contract oversight is the application of penalties and sanctions. However, for this to occur effectively and efficiently, several factors must be taken into consideration, and the public agent is responsible for carrying them out. However, the lack of adequate standards or skills (such as training and qualification) makes these agents challenged when they need to make decisions. In this sense, the main objective of this work was to raise a set of alternatives that serve as a subsidy to public managers in actions aimed at procedures for applying administrative sanctions to companies providing continuous services, in the event of contractual breach. To this end, in the theoretical framework, in addition to the current legislation, a search was carried out in the literature for elements focused on the research topic, which were robust enough to support criteria and subcriteria (attributes) related to the topic, in order to be used in the operationalization of the multicriteria Analytic Hierarchy Process (AHP) method, which served as support for carrying out this work. Regarding the methods and procedures, the approaches used were quantitative, descriptive and cross-sectional, through a survey, which was submitted to the sample online, and the responses were used by the AHP to select attributes that contribute to the management of administrative sanctions in service contracts. Finally, the data obtained by the survey were tabulated and operationalized through the Expert Choice trial version software. As one of the results of the stakeholders' judgments, there was evidence that the creation of technical structures and the implementation of controls are options for managers when it comes to procedures for applying administrative penalties and sanctions. Thus, such alternatives contributed to the preparation of the conclusive technical report as a technical-technological product entitled “Administrative sanctions in service contracts: multicriteria analysis as an aid to management in a federal educational institution” which aimed to deliver a set of alternatives to support managers of the Instituto Federal do Espírito Santo (Ifes) in actions aimed at procedures for applying penalties and sanctions.